Pengembangan Modul Elektronik Pemrograman Berorientasi Objek untuk Siswa Kelas XI Rekayasa Perangkat Lunak dengan Model Four-D - Permani, Angkati; Priyanto, Priyanto (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
This article aims to explain the feasibility of an electronic-based "Making Object Oriented Program with Class" learning module. This study uses an R&D (Research and Development) approach with the Four-D development model. The research population was Grade XI Software Engineering Students of SMK Negeri 1 Rembang Purbalingga. The results showed that each aspect included in the category was very feasible with the average score obtained in the aspect of self-instruction was 3.10, the stand alone aspect was 3.33, the adaptive aspect was 3, the user friendly aspect was 3, the aspect of content eligibility was 3 and the aspect of language has an average of 3.14. Overall material experts show that the material in this module is in the very feasible category with a mean of 3.10 and the percentage of material quality is 77.38%. From these results, it can be stated that this electronic module has fulfilled the characteristics of self-instruction, stand alone, adaptive and user friendly that are appropriate in terms of content and language, so that it can be used in learning.